2011
DOI: 10.1084/jem.20110226
|View full text |Cite
|
Sign up to set email alerts
|

The aminobisphosphonate pamidronate controls influenza pathogenesis by expanding a γδ T cell population in humanized mice

Abstract: As shown in humanized mice, a population of Vγ9Vδ2 T cells can reduce the severity and mortality of disease caused by infection with human and avian influenza viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 68 publications
4
147
0
Order By: Relevance
“…Mouse-adapted influenza virus A H1N1 (A/PR/8/34) (PR8) was cultured in Madin-Darby canine kidney cells as previously described by us (21,22). Virus titers were determined by observation of cytopathic effect in cells infected with serial dilutions of virus stock and further confirmed by hemagglutination assay; the median tissue culture infective dose (TCID 50 ) was calculated according to the Reed-Muench formula.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse-adapted influenza virus A H1N1 (A/PR/8/34) (PR8) was cultured in Madin-Darby canine kidney cells as previously described by us (21,22). Virus titers were determined by observation of cytopathic effect in cells infected with serial dilutions of virus stock and further confirmed by hemagglutination assay; the median tissue culture infective dose (TCID 50 ) was calculated according to the Reed-Muench formula.…”
Section: Methodsmentioning
confidence: 99%
“…22,26,27 Moreover, these antiviral activities can be significantly improved by phosphoantigen stimulation, which confers sufficient protection on humanized mice to prevent lethal influenza virus infection. 28 In addition, another group has shown that cd-T cells can initiate efficient adaptive immunity through processing and presenting influenza virus-derived peptides to CD4 1 and CD8 1 T cells. 29 Moreover, cd-T cells have been found to promote the establishment of protective adaptive immunity against West Nile virus by inducing the maturation of dendritic cells (DCs).…”
Section: Involvement Of Cd-t Cells In Infectious Diseasesmentioning
confidence: 99%
“…Another impediment to studying the efficacy of phosphoantigen activation and expansion of Vc9Vd2 cd-T cells is the lack of an analogue in murine systems, which can be overcome by the development of a humanized mouse model. 28,137 Similarly, reliable animal models need to be established for evaluating the characteristics and clinical potential of human resident cd-T cells in mucosa and skin.…”
Section: Potential Of Cd-t Cell-based Therapy In Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Cytometric bead array analysis PBMCs or CBMCs were infected with influenza A virus at a multiplicity of infection (MOI) of 2 and cultured in RPMI-1640 media supplemented with 10% fetal bovine serum for 24 h. The culture supernatants were collected and cytokine (TNF-a and IFN-c) concentrations were measured using cytometric bead array (Becton & Dickinson, New Jersey, USA) as we described previously. 16 Data were acquired by flow cytometry and analysed with cytometric bead array software. Standard curves for each cytokine were generated to calculate their concentration in the tested samples.…”
Section: Cell Preparation and Influenza Virus Stimulationmentioning
confidence: 99%